Detrimental effects of prior self-control exertion on subsequent sporting skill performance - Boat, R.; Sunderland, C.; Cooper, S. B. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The prior exertion of self-control has previously been shown to negatively affect physical performance, yet the effects on complex sporting skill performance have not been examined. Therefore, this study examined whether prior self-control exertion influences performance on a field hockey task, alongside measuring plasma cortisol concentration and attention as potential mechanisms to explain any effects.